The prognostic importance of the heart function in sepsis and septic shock: a Dedalus or a window of opportunities? - Palmieri, Vittorio; Innocenti, Francesca; Pini, Riccardo (Journal of Emergency and Critical Care Medicine, 2017)
Sepsis is an infection-related clinical condition characterized by severe systemic inflammation, potentially evolving in multi-organ failure through a number of pathophysiological mechanisms. While sepsis is a relatively infrequent disease, it is a world-wide growing and challenging medical issue (1-3), both due to high mortality rate in the short and mid-term follow-ups, and to high costs of medical management (4,5). Hemodynamic instability and sustained hypotension with systemic hypoperfusion not responding to blood volume expansion are the hallmarks of the sepsis-related shock, or septic shock. In sepsis, refractory cardiovascular failure is a frequent cause of fatal events, and myocardial injury can be found in approximately 50% of the patients in necropsy findings (6). Therefore, one cannot infer that sepsis or septic shock is equivalent to myocardial dysfunction.